A pre-embedded brazing agent powder aluminum alloy brazing plate and a preparation method and application thereof
Patent Information
- Application Number
- CN202311525380.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-15
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-11-15
AI Technical Summary
[0005]目前已知预埋钎剂技术,所涉及的钎剂浓度都不超过10%,难以满足需高钎剂克数的产品:如麒麟电池堵片、汽车热交换器堵帽、冷凝器集流管等的焊接要求
[0034]This application provides a method for preparing a pre-embedded flux powder aluminum alloy brazing plate. A high concentration (10-30%) flux is pre-embedded in the brazing layer by a vacuum, high temperature and high pressure powder metallurgy method. Furthermore, the brazing layer with pre-embedded flux in this application does not require milling and can be directly prepared into an aluminum alloy composite material by rolling composite method with the core material and the outer material alloy.
Smart Images

Figure CN117381228B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of aluminum alloy materials technology, specifically to a pre-embedded flux powder aluminum alloy brazing plate and its preparation method and application. Background Technology
[0002] Existing aluminum heat exchangers are typically manufactured using aluminum alloys and their composites via brazing. Because aluminum alloys and their composites are prepared in an atmospheric environment, an oxide film forms on their surface. This oxide film does not wet the molten brazing filler metal, thus inhibiting the flow of the filler metal and capillary adhesion of the solder joints. To achieve a dense bond between the molten brazing filler metal and the surfaces of other materials, this oxide film must be broken, allowing fresh metal to come into contact and wet each other.
[0003] In industrial heat exchanger production, two brazing methods can address the issue of oxide film formation on brazed aluminum alloys. One is controlled atmosphere brazing, typically performed under inert gas protection, where flux is applied or sprayed onto the assembled aluminum alloy surface to dissolve or destroy the oxide film. This method allows for continuous production with high efficiency, and defective products can be re-brazed, resulting in a yield rate as high as 99%. However, it is not suitable for brazing aluminum alloys containing magnesium (Mg). The other method is vacuum brazing, which utilizes the magnesium (Mg) in the brazing plate of the aluminum alloy composite material to dissolve or destroy the oxide film. While vacuum brazing can produce high-quality aluminum alloy components, its production process must be carried out under near-vacuum conditions (3.5 × 10⁻⁶). -3 Brazing in a closed furnace (Pa) results in a long production cycle, low efficiency, and high production cost.
[0004] As aluminum heat exchangers develop towards smaller size, lighter weight, and longer lifespan, the requirements for their aluminum alloy composite materials are becoming increasingly stringent. Controlled atmosphere brazing methods also demand higher uniformity in flux coating or spraying. One effective method to address flux uniformity in brazed aluminum alloy composite materials is to use pre-embedded flux in the brazing layer.
[0005] Currently known pre-embedded flux technology involves flux concentrations of no more than 10%, which is insufficient to meet the welding requirements of products requiring high flux concentrations, such as Kirin battery plugs, automotive heat exchanger plugs, and condenser manifolds.
[0006] Alternatively, powder layers can be formed solely through pressure processing. The resulting powder layer is loosely structured, making it prone to peeling and delamination at the bonding surfaces after subsequent rolling. This leads to inconsistent product quality and low yield. Another method involves directly heating and rolling a powder layer with a border structure. This also results in a loose structure, making peeling and delamination likely. Furthermore, the border width exceeds 100mm, and the sides directly contact the exposed flux, hindering proper coating and fusion. The rolled edges often contain defects requiring trimming, further reducing yield. Both methods are performed in air, resulting in a high overall oxygen content in the powder, which may negatively impact the brazing performance of the finished product. Summary of the Invention
[0007] To address the aforementioned deficiencies in this field, this application aims to provide a pre-embedded flux powder aluminum alloy brazing plate, its preparation method, and its application.
[0008] According to one aspect of this application, a method for preparing a brazing plate for aluminum alloy with pre-embedded flux powder is provided, comprising:
[0009] A silicon-aluminum alloy powder is prepared, wherein the mass fraction of silicon is 6.8-13.0%, and the balance is aluminum;
[0010] The flux powder is mixed with the silicon-aluminum alloy powder to obtain a mixed powder, wherein the amount of flux powder is 10-30% of the mass of the silicon-aluminum alloy powder;
[0011] The shell is made of 4-series aluminum alloy, and the shell thickness is 3-10mm.
[0012] The mixed powder is loaded into the shell, hot isostatically pressed into a blank, and then hot rolled to obtain the brazing plate.
[0013] According to some embodiments of this application, after the mixed powder is loaded into the housing, the housing is further evacuated to 0.5-2 Pa.
[0014] According to some embodiments of this application, the temperature of the hot isostatic pressing blank is 400-500℃, the pressure is 100-150MPa, and the holding time is 3-6h.
[0015] According to some embodiments of this application, the silicon-aluminum alloy powder has a D50 of 10-500 μm;
[0016] The flux powder has a D50 of 2-60 μm.
[0017] According to some embodiments of this application, the mixing speed of the flux powder and the silicon-aluminum alloy powder is 2-6 r / min, and the mixing time is 4-8 h.
[0018] According to another aspect of this application, a brazing board with pre-embedded flux powder is provided, wherein the interior of a 4-series aluminum alloy shell is filled with silicon-aluminum alloy powder and flux powder.
[0019] The silicon has a mass fraction of 6.8-13.0%, with the balance being aluminum;
[0020] The amount of flux powder is 10-30% of the mass of the silicon-aluminum alloy powder;
[0021] The thickness of the shell is 3-10 mm;
[0022] The silicon-aluminum alloy powder has a D50 of 10-500 μm; the flux powder has a D50 of 2-60 μm.
[0023] The thickness of the brazing plate is 5-15mm.
[0024] According to some embodiments of this application, the flux powder is potassium fluoroaluminate.
[0025] According to another aspect of this application, a method for preparing a pre-embedded flux aluminum alloy composite material is provided, comprising:
[0026] Cut the above-mentioned brazing board;
[0027] The layers are stacked in the following order: 4-series alloy - brazing plate - core layer - brazing plate - intermediate layer - brazing plate - 4-series alloy, and then subjected to composite hot rolling, cold rolling, and heat treatment.
[0028] According to some embodiments of this application, the core layer is a 3-series alloy or a 4-series alloy; the intermediate layer is a 3-series alloy.
[0029] According to some embodiments of this application, the composite hot rolling is performed by heating to 450-500℃ and holding for 4-6 hours, with a final rolling temperature greater than 300℃, and hot rolling to 5-8mm.
[0030] The cold rolling is performed to a thickness of 0.05-3.0 mm;
[0031] The heat treatment is performed at 380-400℃ for 2-4 hours.
[0032] According to some embodiments of this application, the composite ratio of the brazing plate is 5-15%.
[0033] Compared with the prior art, this application has at least the following beneficial effects:
[0034] This application provides a method for preparing a pre-embedded flux powder aluminum alloy brazing plate. A high concentration (10-30%) flux is pre-embedded in the brazing layer by a vacuum, high temperature and high pressure powder metallurgy method. Furthermore, the brazing layer with pre-embedded flux in this application does not require milling and can be directly prepared into an aluminum alloy composite material by rolling composite method with the core material and the outer material alloy.
[0035] This application provides a pre-embedded flux aluminum alloy composite material. The composite material has a compact powder layer, uniform flux distribution in the brazing layer, high bonding strength, low oxygen content, high yield, and simple process. It can basically meet the brazing requirements of all aluminum alloy products (products with different flux weight requirements).
[0036] The pre-embedded flux aluminum alloy composite material of this application can shorten the production process of heat exchangers, omitting the three steps of flux and water slurry preparation, flux coating or spraying, and drying. The flux will not remain on the material surface, and it can be completely brazed with other components in controlled atmosphere brazing, which improves the production efficiency of heat exchangers, saves costs, and improves post-weld cleanliness. Attached Figure Description
[0037] Figure 1 This is a flowchart illustrating the preparation process of an example embodiment of this application.
[0038] Figure 2 Metallographic image of the weld foot of the evaporator fabricated by assembling the pre-embedded flux aluminum alloy composite material and fins, which is an example embodiment of this application.
[0039] Figure 3 The image shows the oscillation after filling the inner cavity of the battery direct cooling plate with 60% isooctane or CFC113.
[0040] Figure 4 This is a graph showing the weight of the filter membrane before and after filtration.
[0041] Figure 5 This is a diagram showing the overall particle distribution and the largest metal particle in the sample.
[0042] Figure 6 This is a schematic diagram of the sampling points for cutting the water-cooled plate.
[0043] Figure 7 The material thickness of the pre-embedded flux flow channel plate after stretching in the example embodiment of this application.
[0044] Figure 8 The material thickness of a normal material flow channel plate after stretching is shown as an example comparison of this application.
[0045] Figure 9 Location of explosion failure of pre-embedded flux material and normal material water-cooled plate.
[0046] Figure 10Bursting values of pre-embedded flux material and normal material water-cooled plates.
[0047] Figure 11 Metallographic image of a welding test of a composite material with an oxygen content of <1000 PPM, as an example embodiment of this application.
[0048] Figure 12 Metallographic image of a welding test of a composite material with an oxygen content of 1200 PPM, serving as an example comparative example of this application. Detailed Implementation
[0049] The technical solution of this application will be clearly and completely described below with reference to the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0050] It should be particularly noted that similar substitutions and modifications made to this application are obvious to those skilled in the art, and they are all considered to be included in this application. Those skilled in the art can obviously make modifications or appropriate alterations and combinations to the methods and applications described herein without departing from the content, spirit, and scope of this application to implement and apply the technology of this application. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments.
[0051] Unless otherwise specified, this application is conducted under standard conditions or conditions recommended by the manufacturer. The raw materials or excipients used, as well as the reagents or instruments used, whose manufacturers are not specified, are all conventional products that can be obtained commercially.
[0052] The following is a detailed description of this application.
[0053] Traditional controlled atmosphere brazing methods for producing heat exchangers using coated or sprayed flux-coated aluminum alloy composite materials have the following drawbacks:
[0054] 1) The production process is lengthy. The production process of heat exchangers includes: raw material forming – cleaning – preparation of flux and water slurry – coating or spraying flux – drying – assembly – brazing. This method involves many steps. Furthermore, the coating or spraying method makes it difficult to ensure the flux content at each brazing location on the aluminum alloy composite material, especially for heat exchanger components with complex shapes and structures.
[0055] 2) Flux residue affects appearance and subsequent corrosion performance. Flux is usually a mixture of salts, such as a mixture of potassium fluoride and aluminum fluoride powder. Flux residue after brazing affects the appearance of the heat exchanger and can enter the coolant, accelerating the corrosion of aluminum heat exchangers.
[0056] 3) The flux layer affects precise assembly and positioning. The coated or sprayed flux layer has a certain thickness, which has a certain impact on the assembly and positioning of aluminum alloy composite molded components.
[0057] Currently, it is known that introducing aluminum filler alloy into the flux to replace the traditional surface spraying flux process also has the following disadvantages:
[0058] 1) The flux concentration is low and cannot meet the welding requirements of products that require high flux concentration, such as Kirin battery plugs, automotive heat exchanger plugs, and condenser manifolds.
[0059] 2) Initially, the powder layer is formed solely through pressure processing or by directly adding a frame structure to the powder. Although subsequent heating and rolling are performed, the microstructure is relatively loose, resulting in insufficient bonding strength. The finished product is prone to powder layer detachment at the bonding surface, exhibiting peeling and delamination, leading to unstable product quality and low yield. This is especially true for frame structures, where the frame width exceeds 100mm and the sides directly contact the exposed flux, preventing proper coating and fusion. The rolled edges often have defects, requiring cutting, resulting in extremely low yield. Furthermore, both of these processing methods are performed in air, leading to a high overall oxygen content in the powder, which may affect the brazing performance of the finished product. Existing hot isostatic pressing (HIP) requires subsequent milling and direct mixing with the core material during rolling, which easily causes cracking during the rolling process, also resulting in low yield.
[0060] The method for preparing aluminum alloy composite materials with pre-embedded brazing flux in this application includes:
[0061] 1) Powder preparation: The Si content of aluminum-silicon alloy powder is 6.8-13.0%, the O content is less than 1000ppm, and the powder D50 is 10-500μm. The D50 of potassium fluoroaluminate flux powder is 2-60μm.
[0062] 2) Powder mixing: Weigh 10-30% of potassium fluoroaluminate flux powder, with the remainder being aluminum-silicon alloy powder, and mix them at a low speed of 2-6 r / min on a powder mixer for 4-8 hours.
[0063] 3) Hot isostatic pressing of the blank: A hollow sleeve with an air tube is made of 4-series aluminum alloy. The external dimensions of the sleeve are 55×480×1000mm, of which the 4-series aluminum alloy is 3-10mm thick. The mixed powder is loaded into the sleeve and vacuumed to 0.5-2Pa. The hot isostatic pressing temperature is 400-500℃, the pressure is 100-150MPa, and the holding time is 3-6h.
[0064] 4) Hot rolling: Heat the hot isostatic pressing billet to 450-500℃ and hold for 4-6 hours, then hot roll it to a thickness of 5-15mm to serve as a flux layer.
[0065] 5) Sawing: Cut the ends of the flux plate flat and cut it into plates 350-450mm wide and 4000-5000mm long.
[0066] 6) Assembly and welding: The flux plates are tightly assembled side by side to the required width, and then superimposed and welded with the 3-series core material and 4-series core material. The superposition order is 4-series alloy-flux plate-3-series alloy or 4-series alloy-flux plate-3-series alloy-flux plate-4-series alloy.
[0067] 7) Rolling composite: Heat the assembled blocks to 450-500℃ and hold for 4-6 hours, then hot roll to 5-8mm, with a final rolling temperature greater than 300℃.
[0068] 8) Cold rolling and heat treatment: The hot-rolled plate cooled to room temperature is cold-rolled to 0.05-3.0 mm and then held at 380-400℃ for 2-4 hours to obtain a soft pre-embedded flux brazed aluminum alloy composite material.
[0069] The brazed aluminum alloy composite material of this application has a brazing layer composite ratio of 8-12%. After slitting, stamping or folding, and surface cleaning, it is assembled with aluminum alloy fins, tubes, plates, etc., to form evaporators, condensers, intercoolers, oil coolers, and water-cooled plates. No flux is required; it is directly brazed in a controlled atmosphere, and cooling yields an aluminum heat exchanger. Metallographic inspection of the brazed joints of the heat exchanger shows full weld beads without any incomplete welds. Figure 2 .
[0070] Example 1
[0071] Preparation of the aluminum alloy composite material of this application
[0072] 1) Powder preparation: The Si content of the aluminum-silicon alloy powder is 6.8-8.2%, and the O content is about 200ppm. The powder D50 is 300-500μm, and the D50 of the potassium fluoroaluminate flux powder is 15-60μm.
[0073] 2) Powder mixing: Weigh 10% of potassium fluoroaluminate flux powder, and the remainder is aluminum-silicon alloy powder. Mix them on a powder mixer at a speed of 6 r / min for 4 hours.
[0074] 3) Hot isostatic pressing: A hollow sheath with a gas tube is made of 4343 aluminum alloy, with external dimensions of 55×480×1000mm, of which the 4343 aluminum alloy is 3mm thick. The mixed powder is loaded into the sheath, and a vacuum is drawn to 1Pa. The hot isostatic pressing temperature is 500℃, the pressure is 100MPa, and the holding time is 6h.
[0075] 4) Hot rolling: The hot isostatic pressing billet is heated to 450℃ and held for 6 hours, and then hot rolled to a thickness of 15mm to serve as a flux layer.
[0076] 5) Sawing: Cut the ends of the flux plate flat and cut it into 400mm wide and 5000mm long plates.
[0077] 6) Assembly and welding: The four flux plates are tightly assembled side by side to form a 1200mm thick plate, and then welded to a 430mm thick 3003 core material and a 61mm thick 4343 alloy. The stacking order is 4343-flux plate-3003; the composite ratio of the brazing layer is 15%.
[0078] 5) Rolling composite: The assembled blocks are heated to 450℃ and held for 6 hours, then hot rolled to 6.0 mm, with a final rolling temperature of 310℃.
[0079] 6) Cold rolling and heat treatment: The hot-rolled plate cooled to room temperature is cold-rolled to 1.0 mm and then held at 390℃ for 3 hours to obtain a soft pre-embedded flux brazed aluminum alloy composite material.
[0080] Example 2
[0081] Preparation of the aluminum alloy composite material of this application
[0082] 1) Powder preparation: The Si content of the aluminum-silicon alloy powder is 9-11%, the O content is about 1000ppm, and the powder D50 is 10-100μm. The potassium fluoroaluminate flux powder has a D50 of 2-6μm.
[0083] 2) Powder mixing: Weigh 15% of potassium fluoroaluminate flux powder, and the remainder is aluminum-silicon alloy powder. Mix them at a low speed of 2 r / min on a powder mixer for 8 hours.
[0084] 3) Hot isostatic pressing: A hollow sheath with a gas tube is made of 4045 alloy, with external dimensions of 55×480×1000mm, of which 6mm is 4045 alloy. The mixed powder is loaded into the sheath, and a vacuum is drawn to 2Pa. The hot isostatic pressing temperature is 470℃, the pressure is 130MPa, and the holding time is 4h.
[0085] 4) Hot rolling: The hot isostatic pressing billet is heated to 500℃ and held for 4 hours, and then hot rolled to a thickness of 10mm to serve as a flux layer.
[0086] 5) Sawing: Cut the ends of the flux plate flat and cut it into 400mm wide and 5000mm long plates.
[0087] 6) Assembly and welding: The three flux plates are tightly assembled side by side to form a 1200mm diameter, and then superimposed and welded with a 430mm 3003 core material and a 45mm 4045 alloy. The superposition order is 4045-flux plate-3003-flux plate-4045; the composite ratio of the brazing layer is approximately 10%.
[0088] 5) Rolling composite: Heat the assembled blocks to 500℃ and hold for 4 hours, then hot roll to 5.0 mm, with a final rolling temperature of 300℃.
[0089] 6) Cold rolling and heat treatment: The hot-rolled plate cooled to room temperature is cold-rolled to 0.3 mm and then held at 380℃ for 4 hours to obtain a soft pre-embedded flux brazed aluminum alloy composite material.
[0090] Example 3
[0091] Preparation of the aluminum alloy composite material of this application
[0092] 1) Powder preparation: The Si content of the aluminum-silicon alloy powder is 11-13%, the O content is about 500ppm, and the powder D50 is 100-300μm. The potassium fluoroaluminate flux powder has a D50 of 6-15μm.
[0093] 2) Powder mixing: Weigh 30% of potassium fluoroaluminate flux powder, and the remainder is aluminum-silicon alloy powder. Mix them at a low speed of 4 r / min on a powder mixer for 6 hours.
[0094] 3) Hot isostatic pressing: A hollow sheath with a gas tube is made of 4047 aluminum alloy, with external dimensions of 55×480×1000mm, of which 10mm is 4047 aluminum alloy. The mixed powder is loaded into the sheath, and a vacuum is drawn to 0.5Pa. The hot isostatic pressing temperature is 450℃, the pressure is 150MPa, and the holding time is 3h.
[0095] 4) Hot rolling: The hot isostatic pressing billet is heated to 470℃ and held for 5 hours, and then hot rolled to a 5mm thick plate to serve as a flux layer.
[0096] 5) Sawing: Cut the ends of the flux plate flat and cut it into 400mm wide and 5000mm long plates.
[0097] 6) Assembly and welding: The four flux plates are tightly assembled side by side to form a 1200mm thick plate, and then superimposed and welded with a 430mm thick 3003 core material and a 20mm thick 4047 alloy. The superposition order is 4047-flux plate-3003-flux plate-4047; the composite ratio of the brazing layer is 5%.
[0098] 7) Rolling composite: Heat the assembled blocks to 470℃ and hold for 5 hours, then hot roll to 8.0 mm, with a final rolling temperature of 320℃.
[0099] 6) Cold rolling and heat treatment: The hot-rolled plate cooled to room temperature is cold-rolled to 3.0 mm and then held at 400℃ for 2 hours to obtain a soft pre-embedded flux brazed aluminum alloy composite material.
[0100] Comparative Example 1
[0101] Aluminum alloy composite materials prepared using the method described in this application, but with oxygen content exceeding the standard, are produced.
[0102] 1) Powder preparation: The Si content of the aluminum-silicon alloy powder is 9-11%, the O content is about 1200ppm, and the powder D50 is 10-100μm. The potassium fluoroaluminate flux powder has a D50 of 2-6μm.
[0103] 2) Powder mixing: Weigh 15% of potassium fluoroaluminate flux powder, and the remainder is aluminum-silicon alloy powder. Mix them at a low speed of 2 r / min on a powder mixer for 8 hours.
[0104] 3) Hot isostatic pressing: A hollow sheath with a gas tube is made of 4045 alloy, with external dimensions of 55×480×1000mm, of which 6mm is 4045 alloy. The mixed powder is loaded into the sheath, and a vacuum is drawn to 2Pa. The hot isostatic pressing temperature is 470℃, the pressure is 130MPa, and the holding time is 4h.
[0105] 4) Hot rolling: The hot isostatic pressing billet is heated to 500℃ and held for 4 hours, and then hot rolled to a thickness of 10mm to serve as a flux layer.
[0106] 5) Sawing: Cut the ends of the flux plate flat and cut it into 400mm wide and 5000mm long plates.
[0107] 6) Assembly and welding: The three flux plates are tightly assembled side by side to form a 1200mm diameter, and then superimposed and welded with a 430mm 3003 core material and a 45mm 4045 alloy. The superposition order is 4045-flux plate-3003-flux plate-4045; the composite ratio of the brazing layer is approximately 10%.
[0108] 5) Rolling composite: Heat the assembled blocks to 500℃ and hold for 4 hours, then hot roll to 5.0 mm, with a final rolling temperature of 300℃.
[0109] 6) Cold rolling and heat treatment: The hot-rolled plate cooled to room temperature is cold-rolled to 0.3 mm and then held at 380℃ for 4 hours to obtain a soft pre-embedded flux brazed aluminum alloy composite material.
[0110] Metallographic analysis through welding tests Figure 11 , 12 The comparison showed that the welding quality and porosity of the material with an oxygen content of 1200 ppm were significantly better than those of the normal embedded material with an oxygen content of 1000 ppm, meaning that Example 2 was superior to Comparative Example 1.
[0111] Comparative Example 2
[0112] Aluminum alloy composites are prepared using traditional composite methods that directly produce flux-containing alloy ingots through melting and casting.
[0113] Preparation of alloy ingots: Melting and casting high-Si alloy, Si: 9-11%, flux: 30%
[0114] During the smelting and casting process, the composition was tested and no potassium (K) was found. The analysis indicated that the flux had a melting point of 560℃-570℃, while the smelting temperature reached over 700℃. As a result, the flux had already evaporated and could not remain in the molten aluminum. This plan failed from the very first step.
[0115] Comparative Example 3
[0116] Preparation of aluminum alloy composites using other powder metallurgy methods
[0117] Several commonly used powder metallurgy methods were tried, but none of them could form a metal block. The experiment failed because the flux is non-metallic. If the flux concentration is high, it is difficult for the metal to bond into a block except by hot isostatic pressing.
[0118] Comparative Example 4
[0119] Aluminum alloy composites are prepared using traditional composite methods that directly produce leather ingots through melting and casting.
[0120] 1) Preparation of alloy ingots: Melt and cast national standard 4343 alloy, without flux addition (surface spraying is required if brazing is needed).
[0121] 2) The above alloy ingots are sawed, milled, and heated and rolled to the thickness of the leather material. 3) Assembly: 430mm 3003 core material and 76mm 4343 leather material alloy are stacked, with the stacking order being 4343 leather material-3003; the brazing layer composite ratio is 15%.
[0122] 4) Heat the assembled blocks to 450℃ and hold for 6 hours, then hot roll to 6.0 mm with a final rolling temperature of 310℃.
[0123] 5) Cold rolling and heat treatment: The hot-rolled plate cooled to room temperature is cold-rolled to 1.0 mm and then held at 390℃ for 3 hours to obtain a soft pre-embedded flux brazed aluminum alloy composite material.
[0124] Experimental Example
[0125] 1. The properties of the composite materials in the embodiments and comparative examples of this application were tested, and their structures are shown in the table below:
[0126] Example 1 54.6 122.8 35.0 Example 2 49.9 114.5 35.0 Example 3 63.5 118.7 37.1 Comparative Example 1 48.9 124.4 34.3 Comparative Example 2 / / / Comparative Example 3 / / / Comparative Example 4 56.8 120.3 35.2
[0127] Based on the performance of Example 1 and Comparative Example 4, and Example 2 and Comparative Example 1, it can be concluded that there is no difference in performance between the pre-embedded composite material and the normal composite material.
[0128] 2. Battery cooling plates were prepared using Example 1 and Comparative Example 4 as raw materials, respectively.
[0129] Testing requirements: The weight of soluble matter and solid particles in the battery direct cooling plate ≤ 100 mg / m³ 2 The weight of solid particles in the battery direct cooling plate is <20mg, and the maximum two-dimensional size of the pollutant is ≤0.5mm×0.5mm.
[0130] Testing environment: Temperature (°C): 23±2; Humidity (%RH): 50±5
[0131] Test method: Fill the inner cavity of the battery direct cooling plate with 60% isooctane or CFC113, then place the direct cooling plate on the oscillation table and oscillate at a frequency of 300 times / min for 3 minutes. Then, the solution is recycled into the container, filtered and dried.
[0132] Number of samples: 2 (No. 1# is Example 1, No. 2# is Comparative Example 4, conventional sprayed flux).
[0133] Data recording and analysis: Recording: Measurement was performed using an industrial analytical balance with an accuracy of ±0.1 mg. Residual impurities were observed and tested using a microscope with an accuracy requirement of 0.01 mm (X-axis and Y-axis).
[0134] Test results:
[0135] like Figure 3 The image shown is an oscillation diagram after the inner cavity of the battery direct cooling plate is filled with 60% of the inner cavity volume of isooctane or CFC113. Figure 4 This is a graph showing the weight of the filter membrane before and after filtration. Figure 5 This is a diagram showing the overall particle distribution and the largest metal particle in the sample.
[0136] It is evident that the cleanliness of the battery direct cooling plate brazed with pre-embedded flux in Example 1 of this application meets the requirements, while the battery direct cooling plate brazed with conventional flux spraying (Comparative Example 4) does not meet the requirements (see table below):
[0137]
[0138]
[0139] Figure 6 Sampling points for cutting water-cooled plates; Figure 7 The material thickness after stretching the pre-embedded flux channel plate; Figure 8 The thickness of the material after stretching the normal material flow channel plate.
[0140] The thickness of the pre-embedded flux flow channel plate after stretching is between 0.728 and 0.774 mm. The thickness of the normal material flow channel plate after stretching is between 0.634 and 0.779 mm. The thickness of the pre-embedded flux material is superior to that of the normal material after stretching. It can be seen that the thinning amount and uniformity of the pre-embedded flux material parts in this embodiment are better than those in Comparative Example 4.
[0141] Figure 9Location of explosion failure of pre-embedded flux material and normal material water-cooled plate; Figure 10 Bursting values of pre-embedded flux material and normal material water-cooled plates.
[0142] Depend on Figure 9 Figure 10 It can be seen that the failure locations of the explosive tests in the embodiment and the comparative example are the same. The explosive test value of the embodiment is 3.0 MPa, while that of the comparative example is 2.6 MPa. The explosive test value of the material in embodiment 1 is better than that of the material in comparative example 4.
[0143] Furthermore, the composite material of this application has no impact on the appearance of the heat exchanger or its subsequent corrosion resistance. The flux in this material is uniformly distributed within the brazing layer, so it does not remain on the material surface after brazing. Therefore, it has no impact on the appearance of the heat exchanger and will not enter the coolant and accelerate the corrosion of the aluminum heat exchanger due to surface residue. Moreover, the flux is within the brazing layer of the aluminum alloy composite material and will not affect the assembly and positioning of the molded components.
[0144] The above description of the embodiments is only for the purpose of helping to understand the method and core ideas of this application. It should be noted that those skilled in the art can make several improvements and modifications to this application without departing from the principles of this application, and these improvements and modifications also fall within the protection scope of the claims of this application.
Claims
1. A method for preparing a pre-embedded flux powder aluminum alloy brazing plate for 4-series aluminum alloy composite materials, characterized in that, include: A silicon-aluminum alloy powder is prepared, wherein the mass fraction of silicon is 6.8-13.0%, the balance is aluminum, and the oxygen content is 500-1000 ppm; The flux powder is mixed with the silicon-aluminum alloy powder to obtain a mixed powder, wherein the amount of the flux powder is 10-30% of the mass of the silicon-aluminum alloy powder; The shell is made of 4-series aluminum alloy, and the shell thickness is 3-10mm. The mixed powder is loaded into the shell, hot isostatically pressed into a blank, and then hot rolled to obtain the brazing plate. The silicon-aluminum alloy powder has a D50 of 10-500 μm; The flux powder has a D50 of 2-60 μm; The thickness of the brazing plate is 5-15mm; The 4-series aluminum alloy composite material comprises, in sequence: 4-series alloy - the pre-embedded flux powder aluminum alloy brazing plate - core layer - the pre-embedded flux powder aluminum alloy brazing plate - intermediate layer - the pre-embedded flux powder aluminum alloy brazing plate - 4-series alloy.
2. The preparation method according to claim 1, characterized in that, After the mixed powder is loaded into the housing, the process further includes evacuating the housing to a vacuum level of 0.5-2 Pa.
3. The preparation method according to claim 1, characterized in that, The temperature of the hot isostatic pressing blank is 400-500℃, the pressure is 100-150MPa, and the holding time is 3-6h.
4. The preparation method according to claim 1, characterized in that, The mixing speed of the flux powder and the silicon-aluminum alloy powder is 2-6 r / min, and the mixing time is 4-8 h.
5. An aluminum alloy brazing plate with pre-embedded flux powder prepared by any one of the preparation methods described in claims 1-4.
6. The aluminum alloy brazing plate with pre-embedded flux powder according to claim 5, characterized in that, The flux powder is potassium fluoroaluminate.
7. A method for preparing a pre-embedded flux aluminum alloy composite material, characterized in that, include: Cut the aluminum alloy brazing plate with pre-embedded flux powder as described in any one of claims 5-6; The layers are stacked in the following order: 4-series alloy - brazing plate - core layer - brazing plate - intermediate layer - brazing plate - 4-series alloy, and then subjected to composite hot rolling, cold rolling, and heat treatment.
8. The preparation method according to claim 7, characterized in that, The core layer is a 3-series alloy or a 4-series alloy; the intermediate layer is a 3-series alloy.
9. The preparation method according to claim 7, characterized in that, The composite hot rolling process involves heating to 450-500℃ and holding for 4-6 hours, with a final rolling temperature greater than 300℃, and hot rolling to 5-8mm. The cold rolling is performed to a thickness of 0.05-3.0 mm; The heat treatment is performed at 380-400℃ for 2-4 hours.
10. The preparation method according to claim 7, characterized in that, The composite ratio of the brazing plate is 5-15%.
Citation Information
Patent Citations
Method of making an aluminum alloy brazing agent containing a flux
CN1121855A
Aluminum alloy composite material with pre-buried brazing flux as well as preparation method and application thereof
CN113210608A
Aluminum-alloy brazing sheet, manufacturing method therefor, and brazing method for aluminum heat exchanger
WO2013038934A1